PTH-015 Post-ercp Pancreatitis In Secondary Care: Can We Predict Who Would Benefit From A Prophylactic Pancreatic Stent?. (9th June 2014) - Old, O; Hardy, TJ; Hewin, D; Barr, H; Brown, J
Abstract : Introduction: Pancreatitis is a recognised complication of ERCP. Measures taken to reduce the incidence in high-risk patients include placement of prophylactic pancreatic stents and use of NSAIDs, but current practice varies widely. The frequency of post-ERCP pancreatitis (PEP) in unselected groups ranges from 1.3–6.7% in the largest reported series. Historically, prophylactic stents have not been used at our institution. This retrospective study was designed firstly to measure rates of PEP in our institution (a district general hospital), and secondly to identify those cases which may have benefitted from prophylactic pancreatic stenting. Methods: A retrospective database search identified all patients undergoing ERCP across our Trust over a 5-year period (April 2007 to July 2012). A linked search with a county-wide biochemistry database then identified all those patients who had subsequently developed an elevated serum amylase up to 7 days following ERCP. A consensus grading system was used to define PEP as: clinical pancreatitis (new/worsened abdominal pain), requiring or prolonging hospital admission by ≥2 days, with serum amylase over 3 times upper limit of normal >24 h post procedure (300 units/l). Additional risk factors for post-ERCP pancreatitis were identified: previous PEP, Sphincter of Oddi dysfunction, repeated cannulation, injection of contrast into pancreatic duct, Sphincter of Oddi manometry, balloon dilatation, precut sphincterotomy, or pancreatic sphincterotomy. Results: 2699 patients underwent ERCP during the study period. 6 patients were excluded due to incomplete records. 57 patients with elevated serum amylase went on to notes review, of whom 36 (20 female, mean age 61) were determined to have clinical pancreatitis i.e. 1.3% of all patients undergoing ERCP. Of those with pancreatitis, 4 procedures had a complexity grading of Level 1, 27 of level 2, and 1 case of level 3. In 4 cases the endoscopist was unable to cannulate the CBD. None of the patients received prophylactic NSAIDs at the time of procedure. 3 patients required ITU admission and there were 2 deaths. In 14 cases of PEP (39%), risk factors were present that could be considered an indication for prophylactic stenting, i.e. 0.52% of all patients undergoing ERCP. Conclusion: 2699 ERCP procedures were performed, no prophylactic stents were placed, but pancreatitis occurred as a complication in only 1.3% of procedures. Fewer than half of these patients would have been considered candidates for pancreatic stenting if available. With such a low baseline rate of PEP, the introduction of pancreatic stents should be appropriately selective in high-risk patients only, and NSAIDs considered in all high-risk patients without contraindications. Reference: Freeman ML. Gastroenterol Hepatol 2012;8(9):618–20 Disclosure of Interest: None Declared.